Gene expression and metabolism preceding soft scald, a chilling injury of 'Honeycrisp' apple fruit. (December 2016) - Leisso, Rachel; Gapper, Nigel; Mattheis, James; Sullivan, Nathanael; Watkins, Christopher; Giovannoni, James; Schaffer, Robert; Johnston, Jason; Hanrahan, Ines; Hertog, Maarten; Nicolaï, Bart; Rudell, David
Abstract Background 'Honeycrisp' is an apple cultivar that is susceptible to soft scald, a chilling injury expressed as necrotic patches on the peel. Improved understanding of metabolism associated with the disorder would improve our understanding of soft scald and contribute to developing more effective management strategies for apple storage. It was expected that specific gene expression and specific metabolite levels in the peel would be linked with soft scald risk at harvest and/or specific time points during cold storage. Results Fruit from nine 'Honeycrisp' apple orchards that would eventually develop different incidences of soft scald between 4 and 8 weeks of cold air storage were used to contrast and determine differential transcriptomic and metabolomic changes during storage. Untargeted metabolic profiling revealed changes in a number of distinct pathways preceding and concurrent with soft scald symptom development, including elevated γ-aminobutryic acid (GABA), 1-hexanol, acylated steryl glycosides, and freep -coumaryl acyl esters. At harvest, levels of sesquiterpenoid and triterpenoid acyl esters were relatively higher in peel of fruit that did not later develop the disorder. RNA-seq driven gene expression profiling highlighted possible involvement of genes and associated metabolic processes with soft scald development. These included elevated expression of genes involved in lipid peroxidation and phenolic metabolism in fruit with soft scald, and isoprenoid/brassinosteroid metabolism in fruit that did not develop soft scald. Expression of other stress-related genes in fruit that developed soft scald included chlorophyll catabolism, cell wall loosening, and lipid transport while superoxide dismutases were up-regulated in fruit that did not develop the disorder. Conclusions This study delineates the sequential transcriptomic and metabolomic changes preceding soft scald symptom development. Changes were differential depending on susceptibility of fruit to the disorder and could be attributed to key stress related and mediating pathways.